A Few Billion Lines of Code Later: Using Static Analysis to Find Bugs in the Real World. - BESSEY, AL; BLOCK, KEN; CHELF, BEN; CHOU, ANDY; FULTON, BRYAN; HALEM, SETH; HENRI-GROS, CHARLES; KAMSKY, ASYA; MCPEAK, SCOTT; ENGLER, DAW SON (Communications of the ACM, 2010)
The article discusses the use of static analysis to identify bugs in computer software. Specifically, the authors describe what they learned in the course of commercializing their Coverity Static Analysis bug-detecting software for industrial use. Among topics covered are the unwillingness of some firms to subject all of their code to the author's software, conflicts between their product and other software programs, the necessity of being able to parse code that is to be checked, and firms' occasional indifference to bugs that are discovered.